2004
DOI: 10.1177/001789690406300109
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to explore the challenges of changing children's food and health concepts

Abstract: Objective To investigate the effect of a nutrition education intervention and four hours of related teaching on the nutrition concepts of a sample of 9 year-old children. Design Prepost test design. Children's food classification concepts were assessed before and after the intervention and nutrition teaching. Setting Year 4 class of a suburban primary school in South Wales. Method The children completed a food classification task before and after visiting a health promotion exhibition and receiving lessons emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…For example, Freeman and Bunting [38] found that all of their study participants were knowledgeable about healthy and unhealthy foods and drinks, but they were seemingly unable to apply this knowledge to modify their daily dietary choices. Bullen and Benton [39] concluded that while participants may gain factual knowledge, they do not develop the skills to bring about behavioural change. Despite this, the importance of popularizing nutrition knowledge is essential, and it is widely acknowledged that gaining accurate relevant knowledge is the basis for behavioural changes [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Freeman and Bunting [38] found that all of their study participants were knowledgeable about healthy and unhealthy foods and drinks, but they were seemingly unable to apply this knowledge to modify their daily dietary choices. Bullen and Benton [39] concluded that while participants may gain factual knowledge, they do not develop the skills to bring about behavioural change. Despite this, the importance of popularizing nutrition knowledge is essential, and it is widely acknowledged that gaining accurate relevant knowledge is the basis for behavioural changes [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…A treatment effect was found for the nutrition education and garden group for: ability to identify vegetables; willingness to taste capsicum, broccoli, tomato and pea; and student preference to eat broccoli and pea as a snack HPS, health-promoting school; CT, controlled trial; RCT, randomized controlled trial; PSE, Personal and Social Education; SES, socio-economic status. Radcliffe et al (36) Wind et al (37) Parker and Fox (38) Rana and Alvaro (39) McVey et al (45) Laurence et al (46) O'Brien et al (47) Overall rating* Mullally et al (44) Young (40) Ellis and Ellis (42) Vereecken et al (43) Overall rating* (48) Bullen and Benton (49) Kreisel (50) Vijayapushpam et al (51) Hamilton-Ekeke and Thomas (52) Morgan et al (53) Overall Nutrition promotion using health-promoting schools approach: systematic review Table 2 Continued…”
Section: Before and Aftermentioning
confidence: 99%
“…Arguably, the success of behavior interventions concerning food and nutrition with young children ultimately depends on their understanding of related concepts. Yet, very little is known about how young children think about food, and the development of their understanding of food and nutrition (Zeinstra et al 2007 (Contento 1981;Matheson et al 2002;Stewart et al 2006;Worsley et al 1984;Worsley et al 1983); children's understanding of food and health (Bullen and Benton 2004;Hart et al 2002;Turner 1997); how children classify food into groups (Michela and Contento 1984;Nguyen 2007); as well as influential environmental factors associated with children's food consumption (Yperman and Vermeersch 1979) and food preferences (Beyer and Morris 1974;Birch and Fisher 1998). Among this body of research, a small number of studies have explored children's understanding of food and nutrition concepts based on children's cognitive development (Zeinstra et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these studies describe their findings as they relate to the whole group of participants, rather than presenting the conceptual information from age to age, or in terms of developmental stages. Some studies focus on a specific age group, such as 9-year olds (Bullen and Benton 2004), preschoolers (Matheson et al 2002), 7-and 11-year olds (Stewart et al 2006). These studies, however, were not able to capture the developmental changes in children's understanding of concepts concerning food and nutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation